Disaster education and preparedness in the acute care setting: A cross sectional survey of operating theatre nurse's disaster knowledge and education. (June 2018) - Sonneborn, Olivia; Miller, Charne; Head, Leon; Cross, Rachel
Abstract: Background: Operating theatre services can be heavily relied upon during mass casualty disaster events, which require nurses to have adequate training and education of hospital disaster management plans to respond appropriately. The evidence-base of disaster preparedness in the acute setting is limited, particularly with regard to operating theatre nurses. Objectives: Explore operating theatre nurse's disaster knowledge of their role in a mass casualty event, and identify the preferred mode of disaster education and training to improve disaster preparedness. Design: A cross-sectional research design was employed with data collected using a survey tool. Settings: The research was undertaken on operating theatre nurses in a tertiary hospital in Victoria, Australia. Participants: The participants in this research included 53 operating theatre nurses, 51 Registered Nurses and 2 Enrolled Nurses. Methods: The survey was based on a disaster questionnaire for emergency department nurses from South Australia, exploring knowledge and preparedness for disaster response in the acute setting, and altered to be specific and relevant to the operating theatre environment and broadened to focus on the training needs of perioperative nurses. Results: The survey of 53 operating theatre nurses identified that few had previous disaster experience (19.9%). The majority of respondents were aware of their disaster management policy (Code Brown policy) (94.1%), of reporting lines, and appropriate triage (80.4%). However, a significant number of nurses (50.9%) stated that in the event of a disaster they would "call work to see if [they needed] additional assistance" compared with 43.4% of respondents "wait to be contacted by a manager/floor coordinator" as was policy. Finally, disaster nursing general knowledge amongst staff was poor; a mean of 1.79 (SD = 1.20) correct answers out of a possible 7. Conclusions: This study highlights that disaster education and training methods for disasters be specific to the role required by nurses and all staff during a disaster activation; training drills are preferred although face-to-face education is practical.